2018
DOI: 10.1002/jbm.b.34152
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of a degrading zirconia dental implant 29 months after implantation: Histological and histomorphometrical analysis

Abstract: With the emerging development and improvement of biomaterials, the application of ceramics in restorative medicine has experienced a renaissance. New production processes have reportedly helped to overcome unfavorable biomechanical characteristics of these materials, which lead to a wide application of zirconia as ground material for dental implants. Zirconia-based implants are biocompatible, demonstrate ability to osseointegrate and have a teeth-like color, rendering them to be an ideal replacement for titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Die Entwicklung von neuen funktionalisierten Titanoberflächen, die in der Lage sind, mögliche Probleme im Zusammenhang mit Korrosion/Biotribokorrosion zu minimieren, und/oder von neuen nichtmetallischen Implantatmaterialien ist von größter Bedeutung, um nachteilige Gewebeeffekte zukünftig zu vermeiden. Mit der Entwicklung und Verbesserung von Biomaterialien hat die Anwendung von Keramik in der restaurativen Zahnmedizin eine Renaissance erlebt [41]. In diesem Zusammenhang hat sich die Verwendung von dentalen Implantaten aus Zirkonoxid zu einer Alternative von Titanimplantaten entwickelt [42,43].…”
Section: Biologische Reaktionenunclassified
See 1 more Smart Citation
“…Die Entwicklung von neuen funktionalisierten Titanoberflächen, die in der Lage sind, mögliche Probleme im Zusammenhang mit Korrosion/Biotribokorrosion zu minimieren, und/oder von neuen nichtmetallischen Implantatmaterialien ist von größter Bedeutung, um nachteilige Gewebeeffekte zukünftig zu vermeiden. Mit der Entwicklung und Verbesserung von Biomaterialien hat die Anwendung von Keramik in der restaurativen Zahnmedizin eine Renaissance erlebt [41]. In diesem Zusammenhang hat sich die Verwendung von dentalen Implantaten aus Zirkonoxid zu einer Alternative von Titanimplantaten entwickelt [42,43].…”
Section: Biologische Reaktionenunclassified
“…Zirkondioxid hat außerdem eine Reihe vielversprechender physikalischer und mechanischer Eigenschaften, darunter eine niedrige Wärmeleitfähigkeit, eine hohe Biegefestigkeit (900-1200 MPa), eine angemessene Bruchfestigkeit sowie eine hohe Verschleiß-und Korrosionsbeständigkeit [45,47]. Trotz der vielversprechenden und günstigen Eigenschaften dieses Biomaterials ist jedoch weitere Grundlagen-und klinische Forschung erfor-derlich, um Langzeitergebnisse zu generieren sowie technische und biologische Komplikationen im Zusammenhang mit ihrer Verwendung zu bewerten [41,43,45].…”
Section: Biologische Reaktionenunclassified
“…Zirconium implants are not as predictable as titanium implants. One study found degradation products of a zirconia-based implant only 29 months postoperatively [ 309 ]. Additional alternatives focusing on aesthetics include using a different system whereby the titanium implant’s external colouring is pink, which reduces the potential of soft tissues appearing grey while maintaining the predictability of a titanium implant [ 306 ].…”
Section: Biomimetics Of Periodontal Tissue Engineering and Regenermentioning
confidence: 99%
“…In this context, numerous studies from the fields of orthopedics and oral implantology point to a nano/microparticle-mediated tissue inflammation with subsequent bone loss [ 4 , 5 ]. In case of oral implants, an accumulation of nano/microparticles has been observed in the peri-implant hard and soft tissues around zirconia oral implants [ 5 , 6 , 7 , 8 ]. The assumed mechanisms of particle release are the formation of debris during implant insertion and/or the aging process of zirconia ceramics during their functional period [ 8 ].…”
Section: Introductionmentioning
confidence: 99%